Efficacy of vaccines based on chimeric or multiepitope antigens for protection against visceral leishmaniasis: A systematic review. - Karine Ferreira Lopes; Mariana Lourenço Freire; Silvane Maria Fonseca Murta; Edward Oliveira (PLoS Neglected Tropical Diseases)
Background Visceral leishmaniasis (VL) is an infectious parasitic disease caused by the species Leishmania (Leishmania) infantum in the Mediterranean Basin, the Middle East, Central Asia, South America, and Central America, and Leishmania (Leishmania) donovani in Asia and Africa. VL represents the most severe and systemic form of the disease and is fatal if left untreated. Vaccines based on chimeric or multiepitope antigens hold significant potential to induce a highly effective and long-lasting immune response against infections by these parasites. This review systematically compiles data on the efficacy and protective capabilities of chimeric and multiepitope antigens, while also identifying potential immunogenic targets for vaccine development. Methodology A systematic search was conducted by independent reviewers across four databases to assess the efficacy of vaccines based on chimeric or multiepitope antigens against VL. The review included original studies that reported parasite load or positivity rates in animals immunized with these vaccines and subsequently challenged or exposed to L. infantum infection in preclinical and clinical studies. Key information was extracted, tabulated, and analyzed, with the risk of bias being assessed using the SYRCLE Risk Tool. Principal findings A total of 22 studies were selected, with only one being a randomized clinical trial. Most of the studies were conducted with mice, followed by dogs and hamsters. The reduction in parasite load varied from 14% to 99.6% and from 1.7 to 9.0 log orders. Limiting dilution was the most used method for assessing parasite load, followed by quantitative real-time polymerase chain reaction (qPCR). Most domains had an uncertain risk of bias due to insufficient information described. Conclusions Vaccine formulations containing various chimeric or multiepitope antigens have been developed and evaluated in different preclinical trials, with only one advancing to clinical trials and commercialization. However, the findings of this review highlight the promising potential of chimeric and multiepitope antigens as vaccine candidates against VL. The evidence presented could play a crucial role in guiding the rational development of new studies focused on using these antigens for vaccination against VL.